Enhanced Learning of Mechanical Behavior of Materials via Combined Experiments and nanoHUB Simulations: Learning Modules for Sophomore MSE Students. Issue 1762 (18th February 2015) - Coughlan, Aisling; Johnson, David; Diefes-Dux, Heidi A.; Douglas, K. Anna; Erk, Kendra; Faltens, Tanya A.; Strachan, Alejandro
ABSTRACT: Undergraduate materials engineering students have difficulty conceptualizing the atomic-level processes responsible for plastic deformation. To aid in developing this conceptual understanding, interactive molecular dynamics (MD) simulations were introduced into the sophomore-level materials curriculum, integrating simulation with the traditional tensile testing laboratory. Students perform a tensile test using MD simulations on nanowire samples, and then compare these results with those from the physical tensile tests to develop a visual and more intuitive picture of plastic deformation of crystalline materials.